Regional Autonomy and Development: Evidence from Madhya Pradesh – Chhattisgarh Split in India - Priyaranjan Jha; Karan Talathi (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We exploit the creation of Chhattisgarh (CH) from Madhya Pradesh (MP) in 2000 as a natural experiment to study how regional autonomy affects economic development through administrative proximity and political accountability. Using both difference-in-differences and difference-in-discontinuities designs, we compare villages straddling the new state border before and after the split. Villages in CH near the border experienced significantly faster economic growth—measured by nighttime lights, expansion of private firms and non-farm employment, and improved provision of public goods—than comparable MP villages. These gains are not explained by political stability, party ideology, or migration. Instead, they arise from a more responsive local elite in-charge of the new administration as well as closer proximity to the new state capital, Raipur, which enhanced bureaucratic oversight and political accountability. The results demonstrate that the geography of administration—the distance between citizens and state institutions—can shape development outcomes as powerfully as formal political institutions.
Keywords: D72; H41; H70; H77; O10; O40; 330; state autonomy and control; responsive governance; economic development; proximity; capital; accountability